Differential diagnosis of prion diseases in the vast chapter of degenerative encephalopathies, a challenge for the internist: two case reports compared - Filomena Pietrantonio; Angela Ciamei; Gabriele Angelo Vassallo; Luca Moriconi; Margherita Lordi (Italian Journal of Medicine)
Prion diseases, or transmissible spongiform encephalopathies, fall under the big chapter of differential diagnosis of degenerative diseases of the central nervous system. The cause is prions, which are altered forms of the prion protein (PrP). In pathology, PrP changes its form, becoming a prion, i.e., an infectious protein capable of inducing normal PrP to assume the pathological form. The accumulation of PrP in brain cells creates very small bubbles (vacuoles) that lead to the formation of microscopic holes that make the brain tissue resemble a sponge (hence the term spongiform encephalopathies). These are very rare diseases with a very long latency. After the first symptoms appear, the disease evolves rapidly. There is no treatment, and the outcome is often inauspicious. Two clinical cases of prion disease occasionally found in patients admitted from emergency rooms to the Department of Internal Medicine are described.